INDIVIDUAL AND ERGONOMIC RISK FACTORS FOR MUSCULOSKELETAL DISORDERS AMONG HEALTH WORKERS IN INDONESIA: A LITERATURE REVIEW - Surya, Harleyna; Handayani, Sarah (HEARTY, 2025)
Musculoskeletal disorders (MSDs) affect approximately 1.71 billion people globally, impacting individuals of all ages. The prevalence of MSDs varies by diagnosis and age, and more than 80% of cases occur among healthcare professionals, who are mainly at risk due to their daily work activities. This study aims to identify the individual and ergonomic factors associated with work-related musculoskeletal disorders among health workers in Indonesia. A scoping review focused on scientific journals published between January 2023 and June 2024. The research identified ten studies that met the inclusion criteria set by the authors. The findings indicate that individual risk factors include age and gender, while ergonomic risk factors encompass years of work, workload, work positions, work attitude, and working posture. To mitigate the risk of MSDs, health workers should be mindful of their body positions and take advantage of rest periods to recover, ensuring they can continue working effectively.